Cyber physical systems : design, modeling, and evaluation : 5th International Workshop, CyPhy 2015, Amsterdam, the Netherlands, October 8, 2015 : proceedings /: design, modeling, and evaluation : 5th International Workshop, CyPhy 2015, Amsterdam, the Netherlands, October 8, 2015 : proceedings. ([2015]) - Unknown
No abstract available